Os companheiros de Ulisses, de La Fontaine, e a Odisseia, de Homero: uma proposta de letramento literário para turma do 8º ano - Felix , Izabelly Laura Silva de Souza (2024)
During literature classes in the 8th grade of elementary school, in a school located in the municipality of Gurinhém-PB, the class noticed a need for knowledge about classical texts, since they were an important part of humanity's historical and cultural formation. In view of this, the aim of this work is to offer them literary literacy by presenting a rereading of Homer's Odyssey through La Fontaine's verse fable Ulysses' Companions, written in the 18th century, and Frederico Lourenço's adaptation of the first work, aimed at a young audience, the latter as a way of getting the students to know the narrative from which the fable originated. This is a school intervention project with a qualitative approach, which is configured as action research. The intervention actions will be carried out using the reading circle proposed by Cosson (2014). Kleiman (2005), Cosson (2006) and Soares (1999) are used as the theoretical basis for this work to deal with literary literacy. Portella (1983) and Bagno (2006) to discuss discursive genres and fables. To reinforce the importance of Literature in human life, discussing its function, the ideas of Candido (1967) will be presented. Colomer (2017), Dantas (2013) and the BNCC (2018) will provide support for an approach to the relationship between classical mythology and teaching. Our foundation also includes Calvino (1981), who brings us the essence of classical literature and, finally, Hansen (2006) to explain the concept of allegory, an attribute present in fables; Gregorin Filho (2011), who discusses reading education through mythological narratives, and Eliade (1963) and Grimmal (2013), who bring us the concept of myth. For intervention in the classroom, four moments will be proposed: data collection; reading the fable The Companions of Ulysses and book III of the Odyssey adaptation through the structured reading circle proposed by Cosson; discussion of the text read in order to propose literary literacy practices, and finally, the fourth moment in which the class will be challenged to produce a rereading of the works studied.